Ten Golden Rules for Applying Life Cycle Information - Jim Fava (Indonesian Journal of Life Cycle Assessment and Sustainability, 2019)
We have seen rivers burning, marine litter growing, climate change impacts increasing, limited resources to name a few.  Often our resources are directed towards actions which we create unexpected impacts elsewhere, because we have not considered the full range of impacts along a product life cycle.  Life cycle assessment has increasing become a tool of choice to understand the environmental and social trade-offs associated with product and packaging systems. What have we learned that can accelerate the generation and use of life cycle information to inform decision making?  As we are approaching nearly 30 years of experiences, there is much still to do to develop the capacity and capabilities to generate and use life cycle information to ensure we are working on the right issue, at the right place in the value chain, and by the right groups.    We see a future where products will be designed, manufactured, used and managed at the end of life in ways to create reduced environmental and social impacts than the previous generation.  These innovative products will create business value, e.g., growing revenue, enhancing brand, reducing costs, and mitigating risk). All actors over a product’s life cycle have a role.  New business models will surface.  These outcomes are happening now, but not at the scale needed.  Based upon nearly 30 years of experiences, we have identified Ten Golden Rules for applying life cycle information.  These will be described with examples and guidance on how they can be applied within your own organization.